READING SELF-EFFICACY AS A MEDIATOR BETWEEN READING MOTIVATION AND METACOGNITIVE READING STRATEGIES IN EFL STUDENTS - Gary Collins Brata Winardy; Lucia RM Royanto (Sean Institute, 2022)
Understanding and utilizing literature written in English in studying is a unique challenge many college students face with English as their foreign language. This research seeks to underline the mediating factor of reading self-efficacy between reading motivation and the usage of metacognitive reading strategies that could improve students’ understanding and mastery of study materials that are written in English. This quantitative study involves students in their second year of college education (n=215), that were asked to fill in a reading self-efficacy questionnaire, motivation for reading questionnaire, and metacognitive reading strategy questionnaire. The result reveals that reading self-efficacy is a complete mediator between reading motivation and reading self-efficacy with an effect size of 0.1504, which is significant in α=99% confidence interval. As an implication, reading self-efficacy is crucial to encourage students to use more effective metacognitive reading strategies in their learning.